Penerapan Metode Waterfall pada Sistem Informasi Inventory Berbasis Website - Ananda, Angga Thifal; Butsianto, Sufajar; Sulaeman, Asep Arwan (Journal of Information System Research (JOSH), 2024)
PT. Toa Galva Industries is a company that has been established for more than 47 years, which still uses a manual inventory system such as recording goods data and data on goods in and out using ledgers, causing work to be less efficient and inaccurate. To find out what goods the company owns, the admin must check the goods files one by one so that they are prone to errors in the process. Therefore, it is necessary to create a website-based inventory information system application system that helps companies improve the efficiency and effectiveness of goods management. This system is designed to store data on incoming and outgoing goods and create stock reports quickly and accurately. The Waterfall method is used in designing this system because it has a clear and structured flow, where each stage must be completed before moving on to the next stage. And using the Black Box Testing method. The research results show that this system can help companies manage stock of goods effectively and efficiently, as well as provide fast and accurate reports on goods produced.